(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
There are a number of factors that need the repair or rehabilitation of existing structures, such as increased loads, deterioration due to age or faulty building materials and craftsmanship, or possibly seismic retrofitting. T-beams are comparable to rectangular beams in terms of torsion analysis and design, except that the influence of concrete on the flange is not taken into account. The flange widths of controlled beams were adjusted in order to examine the effect of flange width on torsion resistance. Two more variables being investigated are the orientation of the fibers and the configurations of the strengthening. In trials, GFRP-strengthened beams are compared to control beams that have not been strengthened. According to the study, the torsional behavior of all the GFRP-enhanced T-beams examined was significantly improved. In a test, reinforced GFRP reinforcement shafts are put up against unfortified controls. According to the study, the GFRP reinforcements of the T-bars appear to have undergone a drastic change in tensional behavior or have fallen. In this study, we also take a closer look at fiber arrangements and orientation